A construção discursiva do Nordeste brasileiro em livros didáticos de Geografia - Sátiro, Leandro Nascimento (2018)
Beginning in 1938, the book began to circulate throughout the Brazilian space, carrying in its structure discourses produced by different subjects, which occupy the most different discursive formations. Thus, the book becomes a space of production of meanings inscribed by codes of a certain culture. In this way, the book isn't simply a transmission of knowledge, but a diffusion of ideologies. The ADLF becomes an instrument of fundamental importance for research proposed here, since it's the analysis of a discourse, which seeks to understand and explain how constructs the meaning of a text and how this text articulates with history and society that produced it. Speech is a linguistic and historical object, understanding it requires the analysis of these two elements simultaneously. Therefore, what is said by the subject, will generate different meanings, since these depend of an ideological position that the subject occupies, and this one will speak from discursive formations. Therefore, the proposal of this work isn't to seek a true representation of Northeast, but try to understand the effects of meaning generated by discourses materialized in books from the Analysis of the Speech of Pechetiana French Line, since this dialogue with several areas.